If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (m + -3)(m + -3) = 64 Reorder the terms: (-3 + m)(m + -3) = 64 Reorder the terms: (-3 + m)(-3 + m) = 64 Multiply (-3 + m) * (-3 + m) (-3(-3 + m) + m(-3 + m)) = 64 ((-3 * -3 + m * -3) + m(-3 + m)) = 64 ((9 + -3m) + m(-3 + m)) = 64 (9 + -3m + (-3 * m + m * m)) = 64 (9 + -3m + (-3m + m2)) = 64 Combine like terms: -3m + -3m = -6m (9 + -6m + m2) = 64 Solving 9 + -6m + m2 = 64 Solving for variable 'm'. Reorder the terms: 9 + -64 + -6m + m2 = 64 + -64 Combine like terms: 9 + -64 = -55 -55 + -6m + m2 = 64 + -64 Combine like terms: 64 + -64 = 0 -55 + -6m + m2 = 0 Factor a trinomial. (-5 + -1m)(11 + -1m) = 0Subproblem 1
Set the factor '(-5 + -1m)' equal to zero and attempt to solve: Simplifying -5 + -1m = 0 Solving -5 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1m = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1m = 0 + 5 -1m = 0 + 5 Combine like terms: 0 + 5 = 5 -1m = 5 Divide each side by '-1'. m = -5 Simplifying m = -5Subproblem 2
Set the factor '(11 + -1m)' equal to zero and attempt to solve: Simplifying 11 + -1m = 0 Solving 11 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1m = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -1m = 0 + -11 -1m = 0 + -11 Combine like terms: 0 + -11 = -11 -1m = -11 Divide each side by '-1'. m = 11 Simplifying m = 11Solution
m = {-5, 11}
| m^2-9-64=0 | | 3x-34=2x-5 | | 4/x+1=2x/x+6 | | 195-3x=33x+23 | | 33=6c-3 | | -86-7x=8x+149 | | rd=309d | | 30f=f^2 | | 4(-1x-3)=-52 | | 7(4x+1)=-91 | | 8-7x=x-48 | | -7x-1=-5x-11 | | 6-3x-3x=-12 | | 5x+3+x=-33 | | 5(-8+4x)=160 | | 3(-8+7x)=102 | | 10+4x=x-2 | | 6x-6=-3x-60 | | (-22)-[7+(-6)]= | | -7-5x+3x=13 | | 7x+8+6x=47 | | [(-22)-7]+(-6)= | | (x+a)(x+3)=x^2-2a-15 | | 1=125000+3000x | | 9x^3+6kx^2+(1-3k)x=0 | | (2k-7)(2k-3)=0 | | 7m+21=3+33 | | x^2-4x+k=0 | | 7x-5=10-3x | | 2x-17=-39 | | 5x-4=2-x | | 10s+6=5 |